Quantitative chemical exchange saturation transfer imaging of nuclear overhauser effects in acute ischemic stroke. Issue 1 (7th March 2022) - Msayib, Yunus; Harston, George W. J.; Ray, Kevin J.; Larkin, James R.; Sutherland, Brad A.; Sheerin, Fintan; Blockley, Nicholas P.; Okell, Thomas W.; Jezzard, Peter; Baldwin, Andrew; Sibson, Nicola R.; Kennedy, James; et al.
Abstract : Purpose: In chemical exchange saturation transfer imaging, saturation effects between − 2 to − 5 ppm (nuclear Overhauser effects, NOEs) have been shown to exhibit contrast in preclinical stroke models. Our previous work on NOEs in human stroke used an analysis model that combined NOEs and semisolid MT; however their combination might feasibly have reduced sensitivity to changes in NOEs. The aim of this study was to explore the information a 4‐pool Bloch–McConnell model provides about the NOE contribution in ischemic stroke, contrasting that with an intentionally approximate 3‐pool model. Methods: MRI data from 12 patients presenting with ischemic stroke were retrospectively analyzed, as well as from six animals induced with an ischemic lesion. Two Bloch–McConnell models (4 pools, and a 3‐pool approximation) were compared for their ability to distinguish pathological tissue in acute stroke. The association of NOEs with pH was also explored, using pH phantoms that mimic the intracellular environment of naïve mouse brain. Results: The 4‐pool measure of NOEs exhibited a different association with tissue outcome compared to 3‐pool approximation in the ischemic core and in tissue that underwent delayed infarction. In the ischemic core, the 4‐pool measure was elevated in patient white matter ( 1 . 20 ± 0 . 20 ) and in animals ( 1 . 27 ± 0 . 20 ). In the naïve brain pH phantoms, significant positive correlation between the NOE and pH was observed. Conclusion: Associations of NOEs with tissue pathology were found using the 4‐pool metric that were not observed using the 3‐pool approximation. The 4‐pool model more adequately captured in vivo changes in NOEs and revealed trends depending on tissue pathology in stroke.